Penerapan Posisi Semi Fowler Pada Anak Dengan Sesak Napas Karena Pneumonia - Aida Rizki Kurniawan; IGA Dewi Purnamawati (AKPER Pasar Rebo, 2024)
Background: pneumonia is the leading cause of death in children worldwide with a total of 70% of deaths in the world. The purpose of this study was to obtain an overview of the application of the semi fowler position in nursing care for children with pneumonia. Method: using a descriptive method through a case study approach and literature study where data was obtained through interview techniques, observation and physical examination as well as literature searches. Results: complaints of shortness of breath can be reduced by providing a semi fowler position. The application of Evidence Based Nursing providing a semi fowler position has been carried out on a 3-year-old boy with pneumonia who was treated in the Children's Intensive Care Unit of the Chasbullah Abdul Madjid Hospital, Bekasi City for three days, providing results that the application of the semi fowler position can help reduce complaints of shortness of breath as evidenced by a decrease in respiratory rate and an increase in oxygen saturation in children. Conclusion: Providing a semi fowler position can relieve complaints of shortness of breath so it is important to provide education to parents to take action to provide a semi fowler position to reduce complaints of shortness of breath.